Blocking of Interferon-Induced Jak-Stat Signaling by Japanese Encephalitis Virus NS5 through a Protein Tyrosine Phosphatase-Mediated Mechanism - Lin, Ren-Jye (American Society for Microbiology, 2006)
Japanese encephalitis virus (JEV), a mosquito-borne flavivirus that causes severe human disease, has been shown to block the interferon (IFN)-induced Janus kinase signal transducer and activation of transcription (Jak-Stat) signaling cascade by preventing Tyk2 tyrosine phosphorylation and Stat activation. In this study, we demonstrate that expression of the JEV nonstructural protein NS5 readily blocked IFN-stimulated Jak-Stat signaling events such as Stat1 nuclear translocation and tyrosine phosphorylation of Tyk2 and Stat1. The region of JEV NS5 responsible for Stat1 suppression was identified using various deletion clones. Deletion of 83 N-terminal residues of JEV NS5, but not the 143 C-terminal residues, abolished its ability to block IFN-stimulated Stat1 activation. The role of JEV NS5 as an IFN antagonist was further demonstrated by its ability to block the induction of interferon-stimulated genes and the antiviral effect of IFN-α against the IFN-sensitive encephalomyocarditis virus, which appears to replicate and kill cells that express NS5 even with alpha IFN treatment. Furthermore, the molecular mechanism responsible for IFN antagonism by NS5 probably involves protein tyrosine phosphatases (PTPs), as the IFN-blocking events in both JEV-infected and NS5-expressing cells were reversed by sodium orthovanadate, a broad-spectrum inhibitor of PTPs. We suggest that JEV NS5 is an IFN antagonist and that it may play a role in blocking IFN-stimulated Jak-Stat signaling via activation of PTPs during JEV infection.